The impact of mental health on unintended pregnancies within HIV serodiscordant heterosexual couples in Uganda and Kenya - Lange, Katelyn N (My University, 2019)
Background. Depression among women has important sequelae prior to, during, and after pregnancy. Minimal research has explored the impact of depression on pregnancy incidence. Methods. We used data from the Partners Demonstration Project, an evaluation of integrated PrEP and ART delivery to 1,013 HIV serodiscordant couples in Kenya and Uganda. We administered socio-behavioral questionnaires, including assessment of fertility intentions, “probable depression”, “hazardous” alcohol use, and stigma internalized and perceived, at enrollment and annually for up to 2 years. We used Cox proportional hazards models to assess the association of mental health and incident pregnancy, including separate models for the incidence of unintended pregnancy. Results. Of 1,013 women, 67.0% were living with HIV, 94.6% were married to their study partner, and 56.4% had no children at enrollment. Nearly 20.0% had probable depression at some point during the study and “probable depression” was reported at 9.0% of women’s study visits. We observed 238 incident pregnancies, 29.8% of which were unintended. “Probable depression” was associated with an increased rate of intended (adjusted HR=1.62, 95% CI: 1.12-2.36) and unintended pregnancy (adjusted HR=1.48, 95% CI: 0.73-2.98). Stigma and “hazardous” alcohol use were not associated with pregnancy incidence (adjusted HR=1.15, 95% CI: 0.89-1.49), (adjusted HR=0.81, 95% CI: 0.54-1.21) Conclusions. Women with probable depression were more likely to experience pregnancy. These findings highlight the importance of integrating mental health screening and care into sexual and reproductive health settings in order to reach women who may be experiencing untreated depressive symptoms. Key words: Depression, pregnancy, unintended pregnancy, women, Africa
Thesis (Master's)--University of Washington, 2019
Keywords: Africa; Depression; Pregnancy; Unintended pregnancy; Women; Public health; Women's studies; Psychology; Global Health